Occurrence and Diversity of Giardia duodenalis Assemblages in Livestock in the UK. Issue 6 (8th March 2013) - Minetti, C.; Taweenan, W.; Hogg, R.; Featherstone, C.; Randle, N.; Latham, S. M.; Wastling, J. M.
Summary Giardia duodenalis is a common intestinal parasite in humans and a wide range of livestock species. It is a genetically heterogeneous parasite that has been characterized in seven distinct genetic assemblages or cryptic species, and molecular markers can be used to differentiate both animal‐specific and potentially zoonotic genotypes. Little is known about G. duodenalis and the range of assemblages occurring in domestic livestock species in the UK. Here, we present data on the occurrence and molecular diversity of G. duodenalis detected in the faeces or large intestinal contents of cattle, sheep, pigs, goats and camelids from farms in the north‐west of England. Both healthy and clinically diseased animals were included in the survey. The presence of Giardia spp. and assemblages was determined by sequencing of the small‐subunit ribosomal RNA gene. The potential association of infection with various clinical and epidemiological parameters was studied in cattle using both univariate and multivariate analyses. Giardia spp. were detected in 127 (34.3%) of the 370 animals tested. G. duodenalis assemblage E was found to be predominant in cattle and sheep, followed by assemblage A. Mixed infections with assemblages A and E were also detected. Interestingly, some cattle, sheep and pigs were found to be infected with more unexpected assemblages (C, D, F). Pre‐weaned calves were more likely to test positive than adult animals, but no association between the occurrence of overt intestinal disease and G. duodenalis infection was detected. The common occurrence of assemblage A and the finding of unusual assemblages in atypical hosts suggest that in future, a multilocus analysis should be used to confirm the actual diversity of G. duodenalis in livestock and the presence of potentially zoonotic genotypes. These data also suggest that there is a need to re‐evaluate the clinical significance of G. duodenalis infection in livestock.